Getting a grip on sensorimotor effects in lexical-semantic processing - Heard, Alison; Madan, Christopher R.; Protzner, Andrea B.; Pexman, Penny M. (Springer, 2018)
One of the strategies that researchers have used to investigate the role of sensorimotor information in lexical-semantic processing is to examine effects of words’ rated body-object interaction (BOI; the ease with which the human body can interact with a word’s referent). Processing tends to be facilitated for words with high BOI compared to words with low BOI, across a wide variety of tasks. Such effects have been referenced in debates over the nature of semantic representations, but their theoretical import has been limited by the fact that BOI is a fairly coarse measure of sensorimotor experience with words’ referents. In the present study we collected ratings for 621 words on seven semantic dimensions (graspability, ease of pantomime, number of actions, animacy, size, danger, and usefulness) in order to investigate which attributes are most strongly related to BOI ratings, and to lexical-semantic processing. BOI ratings were obtained from previous norming studies (Bennett, Burnett, Siakaluk, & Pexman, 2011; Tillotson, Siakaluk, & Pexman, 2008) and measures of lexical-semantic processing were obtained from previous behavioural megastudies involving the semantic categorization task (concrete/abstract decision; Pexman, Heard, Lloyd, & Yap, 2017) and the lexical decision task (Balota et al., 2007). Results showed that the motor dimension of graspability, ease of pantomime, and number of actions were all related to BOI and that these dimensions together explained more variance in semantic processing than did BOI ratings alone. These ratings will be useful for researchers who wish to study how different kinds of bodily interactions influence lexical-semantic processing and cognition.